Survival Analysis Of Health Rate Of Covid-19 Patients Using Kaplan-Meier Method At Islamic Hospital In Surabaya A. Yani - Iqbal Firdaus Iqbal; Mursyidul Ibad; Budhi Setianto; Achmad Syafiuddin (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Corona Virus Disease2019 (COVID-19) is a disease that shocked the world at the end of 2019. Based on data, positive cases of Covid-19 in Indonesia on July 29, 2021 reached 3,331,206 people, with 3,240,654 Covid-19 patients recovering and 90,552 Covid-19 patients dying. Meanwhile in the city of Surabaya there were 52,782 confirmed cases with 50,894 patients recovered and 1,888 patients died. The high death rate shows that this virus is dangerous, but the cure rate is also high. A survival analysis is needed to determine the patient's survival time (cured) for Covid-19. This research was conducted non-reactively using secondary data in the form of medical records of Covid-19 patients at the Surabaya A. Yani Islamic Hospital in January-July 2021. The results of the study using the Kaplan-Meier method found that the survival time based on age was 12,423 days, the survival time based on gender was 12,078 days, the survival time based on Early Symptoms was 11,461 days and the survival time based on SpO2 capacity was 16,787 days. The conclusions of this study indicate that, age affects the survival time of respondents where the 27-36 year interval has a better survival time than the other respondents' age intervals. The female sex has a better survival time than the male. Initial symptoms determine the severity and duration of recovery for respondents. SpO2 capacity is directly proportional to the degree of patient safety, the higher the percentage of SpO2 capacity, the greater the chance of survival and the lower the percentage of SpO2 capacity, the lower the expectation.